Characterization of Devcon Plastic Steel Adhesive on Mild Carbon Steel Steel - Viktor Malau; H Hadromi (Faculty of Engineering, Universitas Gadjah Mada, 2003)
The objective of this research is to characterize mechanical and physical behaviors of adhesives bonding (butt and tap joints) on mild carbon steel. The research used an adhesive material of devcon plastic steel. Mechanical properties are tensile sftength, shear strength andtoughness of the joints.The major parameters of this research were adherends surface roughness Ra, adhesive thickness, curing time and curing temperature. Surface roughness of the carbon steel adherends are Ra = 0,52 pm, 0,76 pt and I,2l 1m' Adhesive thichtess varyfrom: 0,03 mm to 0,3 mm and curing time: 1, 2, 3, 4 hours at curing temperatures: 55, 70, 85, 100, 120 and 140 oC. The research has been conducted under static loads at room temperature'The results of static loads (tensile and shear loads) show that adhesive thiclorcss and odherends surface roughness influence signifcantly the strength and toughness of the joints'An increase in the adherends surface roughness will increase adhesive strengths. For certain surface roughness, the joints have an optimunt adhesive thiclorcss that produces a strength and toughness maximum. Heat lreatntent of the joints at curing temperature for certain curing timeinfluences significanlly shear stresses. An increase of curing time will increase shear stresses' At certain surface roughness and curing time (for example: Ra : 0,76 pn and curing time = 4 hours), this research shows that the joints have an optimum curing temperature. Specimenscured at elevated temperqture show generally the increasing strength, however there is an optimum temperature where cure exceed this temperature the strength begins decrease. idhesives bonding failure of butt joints are generally cohesive and lap joints have a mixed failure cohesive and adhesiveKeywords: adhesive bonding, mild carbon steel, devcon plastic steel, static load, butt joints.